Anxiety levels and quality of life in students from a Private University in Arequipa - Villanueva Kuong, Leslie Emilia (2017)
The objective of this research was to determine the relationship between anxiety levels and the quality of life categories of the young students from a private university in Arequipa. The research design is non-experimental, cross-correlational. The random sample was made up of 448 youngsters aged 20 to 24. The instrument used was: Zung’s Anxiety Self-Assessment Scale (EAA) and the Olson & Barnes Quality of Life Scale. Statistical analysis was performed for categorical data, according to the curve of distribution obtained. The results indicate absence of anxiety in the young investigated, however, the most marked category is the poor quality of life of young people. Finding that there is no significant relationship (p> 0.05) between anxiety levels and quality of life. However, the absence of anxiety was significantly (p< 0.05) slightly negative with the indicators household and economic well-being, family life and extended family, health, and there was a slight positive relationship with the media indicator.